Forage productivity of nopal varieties (Opuntia spp.) under different soil moisture regimes - Bacarrillo-López, Roberto; Pedroza-Sandoval, Aurelio; Inzunza-Ibarra, Marco Antonio; Flores-Hernández, Arnoldo; Macías-Rodríguez, Francisco J. (Ecosistemas y Recursos Agropecuarios, 2021)
The objective of this study was to evaluate the growth and biomass production of Opuntia varieties in different soil moisture content as an alternative for forage production. A randomized block experimental design was used in an arrangement of split plots with three replications. The large plots were the soil moisture content: very favorable (22 - 27%), favorable (16 - 21%) and unfavorable (10 - 15 %); the small plots corresponded to the varieties of nopal: Chapingo (Ch) Narro (N) and Escobar (E). Chapingo variety was statistically higher (P < ó = 0.05) in width and thickness of cladodes in the favorable and very favorable soil moisture content, with values of 15.7 and 1.1 cm and 15.2 and 1.0 cm, respectively; Escobar and Narro varieties were the ones that registered the highest relative water content (RWC) in the favorable and unfavorable moisture content, with values of 78.1 and 63%, respectively. The chlorophyll index did not change due to the effect of any of the variation factors of this study. Narro variety was the one with the best productivity in the soil moisture content more favorable, with values of 1.77 kg and 173.5 g of fresh and dry biomass per plant, equivalent to 11.8 and 1.15 t ha?1 of fresh and dry biomass, respectively, in cladode cut after eight months after the transplant.